Immunoregulation in bovine parasitic infection, mechanisms and implications - Sulaiman, Azad A (2016)
One of the characteristic features of parasitic infections is the chronicity and persistence of the infection for long time. Their success is due to its ability to deviate the immune response of their host toward the immunoregulatory or immunosuppressive state. IL-10 is a multifunctional cytokine with both immunosuppressive and immunostimulatory effects during parasite infection, playing a crucial role in the regulation of the immunity by ameliorating the destructive immunopathology associated with excessive inflammation but often suppressing effective immune responses against pathogens and impairing parasite clearance. Several transcription factors have been characterised that act on the promoter region of human and mouse IL-10 and their role in the transcription of this cytokine has been experimentally verified. In our study, a 570 bp fragment of the 5' UTR region flanking the bovine il-10 gene was cloned and characterised by sequencing. Several SNPs relative to the reference sequence are described, the putative polymorphisms lie within the transcription factor binding sites Sp1, Cap, HSF, ADR1, MZF1, GATA1 and Hb. We have investigated the role of GATA1 in regulation of IL-10 expression from fluke naïve PBMCs in response to LFH and FhTLM and we demonstrate that both LFH and FhTLM treatment induced GATA1 expression from PBMCs. These molecules showed distinct effects on PBMC functions i.e. stimulation of IL-10 in response to FhTLM and inhibition when LFH is used. However, both factors inhibit PBMCs proliferation and IFN-γ expression. We have also found that FhTLM binds to bovine TGFβ-RIED and TGFβ-RIIED fusion proteins but with a higher avidity to TGFβ-RIIED. These results highlight the role of FhTLM as a potent immunomodulatory of the bovine immune system by binding to bovine cytokine receptors. Neospora caninum infection is the major cause of abortion in dairy cattle. Infection with this parasite leads to a polarized Th1 response with high IFN-γ and IL-12 which provide protection aginst N. caninum infection. We have determined the effects of IL-10 in the regulation of IFN-γ and its association with production parameters (milk yield, lactation numbers) by measuring the levels of these cytokines in serum of infected animals and relating these to the key production parameters. Our results have shown that 84 % of high seropositive dams gave birth to seropositive calves and IL-10 concentration was higher in seropositive animals compared to seronegative. However, no correlation was found between the IL-10 concentration of seropositive dams and their calves. Together these indicated that IL-10 is an important cytokine during neosporosis, which modulate the immune response and allow the transmission of the infection to the offspring. Finally, our results for association of the IL-10 with lifetime daily yield demonstrated that IL-10 has a negative association with milk production during infection with N. caninum. Results of our study demonstrate a key role for bovine IL-10 in the regulation of multiple facets of parasite infection and immunity.